Effect Of Additional Variations Of Etanol Fuel On Exhaust Gas Emissions On Yamaha 125cc Motorcycles: Pengaruh Variasi Penambahan Bahan Bakar Etanol Terhadap Emisi Gas Buang Pada Sepeda Motor Yamaha 125cc - Nur Afif Rozikin; Rachmat Firdaus (Universitas Muhammadiyah Sidoarjo, 2021)
The very rapid development of the automotive world nowadays has made it a daily necessity for the community, in everyday human life it cannot be far from the name automotive, both in terms of transportation, and all kinds of supporting household needs. This can be seen from the number of motorbikes operating more when compared to other types of land transportation vehicles such as: cars. As we know, all transportation vehicles today still use non-renewable fuels. In line with the growing demand for fuel in the transportation, industrial and household sectors. Then this will result in unfavorable impacts on the environment, namely the residual exhaust gases from combustion. The remaining exhaust gases cause air pollution which can pollute the environment and can even destroy ozone which is very useful for living things on earth. In this study we use a reference concept which is then used as a concept, how is the effect of variations in the addition of ethanol fuel to exhaust gas emissions of Yamaha 125cc motorcycles by using variations in the percentage of ethanol 10%, 20%, 30% and variations in engine speed during testing, at 4600rpm, 5700rpm, and 6200rpm. It was found that the best torque and power were produced at a percentage of 10% ethanol at 6200 rpm indicating a power of 6.4 Hp and a torque of 10.6 Nm, and the best results on 30% preentae ethanol at 4600rpm showed 0.01% CO gas, 37 ppm HC gas, 1.8% CO2 gas and 18.06% O2 gas.